Exercise-induced skeletal muscle angiogenesis: impact of age, sex, angiocrines and cellular mediators - Ross, M.; Kargl, C. K.; Ferguson, R.; Gavin, T. P.; Hellsten, Y. (European Journal of Applied Physiology, 2023)
Exercise-induced skeletal muscle angiogenesis is a well-known physiological adaptation that occurs in humans in response to exercise training and can lead to endurance performance benefits, as well as improvements in cardiovascular and skeletal tissue health. An increase in capillary density in skeletal muscle improves diffusive oxygen exchange and waste extraction, and thus greater fatigue resistance, which has application to athletes but also to the general population. Exercise-induced angiogenesis can significantly contribute to improvements in cardiovascular and metabolic health, such as the increase in muscle glucose uptake, important for the prevention of diabetes. Recently, our understanding of the mechanisms by which angiogenesis occurs with exercise has grown substantially. This review will detail the biochemical, cellular and biomechanical signals for exercise-induced skeletal muscle angiogenesis, including recent work on extracellular vesicles and circulating angiogenic cells. In addition, the influence of age, sex, exercise intensity/duration, as well as recent observations with the use of blood flow restricted exercise, will also be discussed in detail. This review will provide academics and practitioners with mechanistic and applied evidence for optimising training interventions to promote physical performance through manipulating capillarisation in skeletal muscle.